Acute responses to repeated-sprint training in hypoxia combined with whole-body cryotherapy: A preliminary study - Mihailovic, T.; Groslambert, A.; Bouzigon, R.; Feaud, S.; Millet, G. P.; Gimenez, P. (International Journal of Sports Physiology and Performance, 2024)
Purpose: This study aimed to investigate acute psychophysiological responses to repeated-sprint training in hypoxia (RSH) combined with whole-body cryotherapy (WBC).